THEORETICAL STRATEGIES TO TEACHING ENGLISH TO DEAF STUDENTS - Nabiyeva Nodira Rustamjon qizi (Ecomind Press, 2025)
This article highlights the theoretical princip and strategies to teaching English to students with disabilities. Moreover, in this article was given problems and it's solutions of learning English to students with disabilities.
Keywords: Student with disabilities, sign language alphabet, deaf, blind, method, strategy.